Paradigms unfolded – developing, validating, and evaluating the Medical Education e-Professionalism framework from a philosophical perspective - Guraya, Shaista Salman; Harkin, Denis W.; Yusoff, Muhamad Saiful Bahri; Guraya, Salman Yousuf (Frontiers in Medicine, 2023)
In order to ensure a strong research design, literature stresses the adoption of a research paradigm that is consistent with the researcher's beliefs about the nature of reality. In this article we provide an overview of research paradigm choices in relation to the creation of a Medical Education e-Professionalism (MEeP) framework discussing the research design, research methods, data collection and analysis to enhance the transparency of our previously published research. The MEeP framework was conceived to help Health Care Professionals (HCPs) safeguard the construct of professionalism in the digital context. This entire process was heavily informed by wider readings and deliberations of published literature on e-professionalism. Although the MEeP framework research journey has been published, the paradigms approach was not discussed in any detail. Considering that one of the duties of medical educator is to balance the service and science by bringing the theoretical underpinnings of one's research to public attention and scrutiny so as to nullify the notion of 'weak' research. We were compelled to unfold this paradigm story of the MEeP framework in a detailed manner. In an effort to make our research both robust and effective, this study portrays a philosophical approach to guide future research designs and methodological choices by detailing our rationale for pragmatism as a choice of paradigm.